The Effect of Equal Employment Opportunity on Faculty Retention and Performance in Higher Education - Priya Kaushik, Manoj Agarwal (Journal of Informatics Education and Research, 2024)
Equal Employment Opportunity (EEO) policies are vital for fostering fairness, inclusion, and non-discrimination within the workplace, particularly in higher education. This research paper explores the impact of EEO policies on faculty retention and performance. Utilizing a mixed-methods approach, the study analyzes the relationship between EEO practices and key metrics, including faculty retention rates, research output, and teaching quality. The results indicate that effective EEO policies significantly enhance faculty retention and performance, with particularly positive effects observed among historically underrepresented groups. Statistical analyses, including correlation and regression, validate these findings, revealing that institutions with strong EEO practices not only retain talented faculty but also improve their research and teaching effectiveness. This study underscores the importance of implementing robust EEO policies to foster an equitable and supportive academic environment, ultimately benefiting both faculty members and the institutions they serve.